Pendekatan Pentahelix dalam Tata Kelola Desa Wisata Berkelanjutan di Desa Bantaragung Kabupaten Majalengka - Kuswandi, Aos; Al Rasyid, M. Harun; Nuraini, Siti; Nurul Sa’diyyah, Zulfanida (Jurnal Pemerintahan dan Politik, 2025)
The development of sustainable tourism villages is an important focus in tourism development in Indonesia. Bantaragung Village in Majalengka Regency possesses both natural potential and community traditions that are conducive to development. This research aims to analyze the development of sustainable tourism villages in Bantaragung Village using the pentahelix approach. The research employed a qualitative method, utilizing descriptive narrative analysis. The findings of this study indicate that effective collaboration among the government, private sector, community, academic institutions, and media has been instrumental in the establishment of sustainable tourism villages. The community plays a pivotal role in the sustainability of the tourism village, while the village government establishes the management policy. The private sector has been instrumental in facilitating infrastructure development, including the establishment of homestays, roads, and local transportation systems. Universities contribute to the advancement of sustainable tourism village development models through academic studies. Finally, social media was identified as the primary promotional tool to introduce Bantaragung Village's tourism potential to a broader audience.